2018
DOI: 10.1002/acp.3480
|View full text |Cite
|
Sign up to set email alerts
|

Does alcohol loosen the tongue? Intoxicated individuals' willingness to report transgressions or criminal behavior carried out by themselves or others

Abstract: Police commonly interview intoxicated suspects. This is concerning when suspects are innocent because intoxication often leads to a higher risk for impulsive decision making and reduces inhibition. However, the manner in which intoxication affects people's reporting of unethical or criminal actions carried out by themselves or others is unknown and was thus addressed in the current study. Participants (N = 116) were randomly assigned to one of six conditions based on a 2 (transgression: self, other) × 3 (alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…The intoxicated individuals were able to inhibit their responses when they needed to. Mindthoff et al (), similarly, found that intoxication did not predict transgression disclosure, also indicating that intoxicated individuals were able to inhibit disclosures, which does not support the disinhibition mechanism either.…”
Section: Four Mechanismsmentioning
confidence: 96%
See 4 more Smart Citations
“…The intoxicated individuals were able to inhibit their responses when they needed to. Mindthoff et al (), similarly, found that intoxication did not predict transgression disclosure, also indicating that intoxicated individuals were able to inhibit disclosures, which does not support the disinhibition mechanism either.…”
Section: Four Mechanismsmentioning
confidence: 96%
“…They may have only encoded salient cues, causing them to be more susceptible to suggestions about other cues to fill in the gaps, which supports alcohol myopia as the underlying mechanism. Mindthoff et al () did not find support for alcohol myopia as intoxication was shown not to predict transgression disclosures; the intoxicated group was able to process the negative consequences of disclosing, which can be considered as peripheral information, as efficiently as the control group. Meanwhile, Sauerland et al () argued that, based on the AMT's automatic allocation of the limited resources towards salient cues, intoxication would not affect an individual's ability to discriminate salient cues.…”
Section: Four Mechanismsmentioning
confidence: 97%
See 3 more Smart Citations